Race and the politics of fear - Hubler, J. Noel, author. aut Link Link
1 online resource.
Keywords: "Race and the Politics of Fear is a study of the role of race in American political history. It takes a novel approach by using Aristotle's theory of the mixed regime to analyze the American system. Aristotle's mixed regime-containing elements of oligarchy and democracy-was well-known to the Founders, who used it to design the Constitution. Accordingly, American political history has unfolded as a struggle between oligarchic and democratic forces. Oligarchs have frequently used race to divide the people and maintain power. This book traces the oligarchic construction of race from its creation in the Colonial period and through a study of four major figures. James Madison helped formulate the Constitution to provide protection for the Southern oligarchies and was a founder of the Democratic-Republican party dominated by Southern interests. John C. Calhoun's theory of the concurrent majority provided a blueprint for the South's political strategy in the Jim Crow era. Ben Tillman redefined race primarily as a feeling as an excuse for the South's violent oppression of the black community. Ronald Reagan retooled the traditional racist myths and made them palatable to a national audience. Readable yet extensively documented, it is appropriate for general audiences and scholars"-- Provided by publisher.